(untitled) (BIRDEM Medical Journal, 2017)
Tuberculosis (TB) is a common infectious disease in developing countries like Bangladesh. Drug-resistant tuberculosis (DR-TB) poses a significant threat to the population. A relatively uncommon site of involvement of TB is adrenal gland, which is an important cause of chronic adrenal insufficiency. Here we present a case of a 40-year-old male with multidrug-resistant tuberculosis (MDR-TB) involving the adrenal glands. He was previously diagnosed as a case of disseminated TB involving lungs, right knee joint and lumbar spine and received anti-TB chemotherapy for several occasions and in different categories in last 12 years before this presentation. He presented with 4-month history of vomiting, diarrhea, generalized weakness, generalized pigmentation and postural hypotension. Investigations revealed hyponatremia with hyperkalemia. Adrenal insufficiency was suspected and serum cortisol was found to be low and serum adreno corticotropic hormone (ACTH) was high. On imaging there was bilateral adrenal enlargement. Fine needle aspiration cytology (FNAC) was done from adrenal gland which revealed granulomatous lesion suggestive of TB. Gene Xpert and culture-sensitivity of aspirated material for Mycobacterium tuberculosis revealed MDR-TB. Patient was finally diagnosed as a case of primary adrenal insufficiency due to MDR-TB of the adrenal glands and was treated with regime for MDR-TB for 20 months. Birdem Med J 2017; 7(3): 235-237